Assessing the effect of industrial wastewater on soil properties and physiological and nutritional responses of Robinia pseudoacacia, Cercis siliquastrum and Caesalpinia gilliesii seedlings. (1st July 2018) - Aman, Maryam Saffari; Jafari, Mohammad; Reihan, Majid Karimpour; Motesharezadeh, Babak; Zare, Salman
Abstract: The main aim of this study is to investigate the physical and chemical properties, including soil salinity, acidity, concentrations of macro-nutrients (phosphorus, potassium, and Calcium-Magnesium) and sodium adsorption ratio to the soil, physiological and nutritional traits of three plant species including Caesalpinia gilliesii, Robinia pseudoacacia, and Cercis siliquastrum . First, some sample were taken from the agricultural soils irrigated with wastewater. The results of initial soil test revealed that the irrigation with wastewater significantly increased sodium adsorption ratio (SAR), electrical conductivity (ECe), cation exchange capacity (CEC) of the soil (p < 0.05). Secondly, the effect of industrial wastewater on the responses of three plants were investigated. According to the results, the highest shoot fresh weight was observed in C. gilliesii seedlings treated with T100%, which is 35% higher than the control treatment. The highest concentration of shoot phosphorus in the three plants was respectively 0.54, 0.72, and 1% in those treated with T100% and 0.41, 0.48, and 0.83% in the control treatment. The amount of shoot potassium in the three plants treated with T100% was respectively 0.84, 0.48, and 1%, while it was 0.43, 0.4, and 0.1 in the control treatment, respectively (p < 0.05). According to the current concerns about increased EC, SAR, and Na in C. gilliesii treated with T100%, as compared to the control treatment (50, 386, and 412), and the positive effects of wastewater on soil properties (CEC, pH, and K) and morpho-physiological responses of the plant, it is recommended to use wastewater with continuous monitoring to prevent the pollution of water and soil resource. Highlights: The highest shoot fresh weight, EC, SAR, and Na were observed in Caesalpinia gilliesii treated with T100% Wastewater. Irrigation with wastewater is more efficient than the use of normal water. Wastewaters usually are a good source of nitrogen, potassium, phosphorus, and other essential elements for plant growth. Application of treated wastewater for irrigation, may supply water for ornamental plants and greenery trees, add organic matter and nutrients required by the plant to the soil.